The rice economies : technology and development in Asian societies - Bray, Francesca (University of California Press, 1994)
Wide-ranging both historically and geographically, The Rice Economies brilliantly addresses a subject of abiding interest to anthropologists, economists, and historians as well as those concerned with development issues and Asian studies. It is the first work to formulate a logical, historical dynamic of development in Asia's rice economies up to the present day. The comparison of mechanized Western farming methods with the more labor intensive, less environmentally destructive Asian methods is of value to environmentalists and economists concerned with the need for sustainable development. In a new preface, the author reflects upon the increasing relevance of the concerns of the book to international environmental issues
Originally published: Oxford; New York : Blackwell, 1986. With a new preface
Keywords: Rice trade -- Asia.; Rice -- Technological innovations -- Asia.; Asia -- Economic conditions -- 1945-; Agriculture -- Economic aspects -- Asia.; Riz -- Commerce -- Asie.; Riz -- Innovations -- Asie.; Asie -- Conditions économiques -- 1945-; Agriculture -- Aspect économique -- Asie.; BUSINESS & ECONOMICS -- Industries -- Agribusiness.; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture.; HISTORY / Asia / General; Rice -- Technological innovations; Agriculture -- Economic aspects; Economic history; Rice trade; Asia; Rijstbouw.; Economische situatie.; Azië; Since 1945